Dynamic changes in the use of online advice in response to task success or failure. Issue 10 (2nd October 2016) - Phillips, James G.; Landon, Jason
ABSTRACT: A range of responsible gambling systems have been developed, but they are not necessarily used by consumers. This requires an understanding of factors (e.g. risk and loss) influencing response to advice. Therefore, an experiment examined the use of decisional support in response to induced success or failure. A total of 21 university students played computer Blackjack at two levels of risk, and were informed as to whether the odds were in their favour ('card count'), and were given online advice as to card selection (Basic). Winning streaks led to overconfidence, as indicated by larger mean bets, more Basic errors, and a failure to adjust wagering upon cessation of the winning streak. Participants were more cautious in response to losses, betting less, and were more likely to comply with advice. Participants attended and complied with advice earlier at low risk, but at high risk noticed advice later and did not comply. Induced emotional states (e.g. winning or losing) are important as they influence the likelihood that people will listen to online advice. Designers of Behaviour Change Support Systems should consider methods of contingently implementing advice.